EFEKTIVITAS PROGRAM P5 BERBASIS KEARIFAN LOKAL DALAM MENGATASI KESULITAN BELAJAR DI SEKOLAH DASAR - Arifin, Iqbal; Irmawati M; Ulyatur Rifqah; Putri Ayu Mardhatillah; Nuraeni Arbani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study evaluates the effectiveness of the local wisdom-based Pancasila Student Profile (P5) Strengthening Program in overcoming learning difficulties and improving student academic achievement in elementary schools in Polewali Mandar Regency. The P5 program is implemented by utilizing local values such as gotong royong, responsibility, and respect for others. This study used a qualitative method with a descriptive approach, involving 20 informants consisting of teachers, students and parents. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis method.The results showed that the implementation of local wisdom-based P5 was effective in helping students overcome learning difficulties through project-based activities and hands-on experiences. Students who were originally passive and experienced learning difficulties became more active and motivated in participating in learning. In addition, P5 is also proven to improve students' academic achievement, especially in science, math, art and history subjects. Activities relevant to students' daily lives, such as environmental projects, traditional food making and museum visits, help students understand abstract concepts better. Overall, the P5 program contributes to improving the quality of learning in Polewali Mandar district by creating a learning environment that is relevant, contextual, and supports students' character development in accordance with the values of Pancasila.